A influência da educação de nível superior no conhecimento financeiro e na atitude da tomada de decisão financeira - Silva, Nizomário Tayron Ferreira (Universidade Federal Rural do Semi-Árido, 2019)
The present study has for objective to analyze the influence of the administration courses and accounting sciences about the level of financial knowledge and the attitudes in the socket of financial decision of the administration students and accounting sciences of two public universities of the interior of Rio Grande do Norte. It will be studied the university students of the administration courses and accounting sciences by the fact of the grating curriculum of those courses to provide great sharing of financial knowledge. The research universe understands 1197 students and the sample consisted of 509 students of the administration courses and accounting sciences of two universities of the interior of the semi-arid, being a federal one and a state one. The method of determination of the size of a sample considered the finite universe, respecting the level of trust of 95% and margin of error samplel 5%. the analysis of the data was accomplished through statistical evaluation with base in the software SPSS, and the results were compared by students among the different apprenticeships of the researched degree courses, in agreement with the variables: knowledge level and the individuals' attitude in relation to their financial decisions as well as socioeconomic profile. To verify the significant among the results obtained with to present research and the expected data, the no-parametric, qui-square statistical test was applied. In this research, it was presented that it exists her the influence of the administration courses and accounting sciences about the level of financial knowledge and the attitudes in the it makes of decision of the students, once the difference of the results courses and financial knowledge as the liquidity of assets and investments; And the difference between the courses and financial knowledge as for financings of goods they had association significant estatistician and they need to be better studied in future researches.
Monografia
Keywords: Nível de conhecimento financeiro; Atitudes na tomada de decisão financeira; Rio Grande do Norte; Universitários; Influência; Level of financial knowledge; Attitudes in the socket of financial decision; Rio Grande do Norte; Academical; Influence; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO